Comparative Analysis of Arima and Facebook Prophet Algorithms for E-Commerce Product Sales Forecasting - Ersha Thoriq Ferdinansyah; Muhammad Roffi; Rafi Ramadhan; Elyandri Prasiwiningrum (Journal Collabits, 2026)
Uncertainty in market demand poses a fundamental challenge in e-commerce supply chain management. This study evaluates the accuracy of daily sales forecasting for the